2017
DOI: 10.1007/s00330-017-4750-y
|View full text |Cite
|
Sign up to set email alerts
|

Clinical implications of nonspecific pulmonary nodules identified during the initial evaluation of patients with head and neck squamous cell carcinoma

Abstract: • We aimed to identify the clinical implications of nonspecific pulmonary nodules (NPNs). • NPNs in head and neck cancer patients do not lead to pulmonary malignancies (PMs). • NPNs are not associated with overall or PM-free survival (PMFS). • Cervical lymph node involvement is an independent prognostic factor affecting PMFS. • Platelet-lymphocyte ratio ≥126 is another predictor of PMFS regardless of NPN presence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…Kwon et al reported that the cumulative incidence rates of pulmonary malignancy development at 2 years after treatment of HNSCC were equivalent regardless of whether non-specific pulmonary nodules were present during the initial staging workup. 17 Advanced primary stage and primary cervical lymph node (LN) involvement were independent factors for pulmonary malignancy development, and they led to the hypothesis that the lower cervical LN near the thoracic space would be at significant risk for lung metastases based on the “cascade theory”, which infers that some adjacent sites are seeded first and that further metastases proceed in sites other than the primary site. 17 Additionally, primary cervical LN involvement was demonstrated to be a poor prognostic factor after PM for HNSCC.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Kwon et al reported that the cumulative incidence rates of pulmonary malignancy development at 2 years after treatment of HNSCC were equivalent regardless of whether non-specific pulmonary nodules were present during the initial staging workup. 17 Advanced primary stage and primary cervical lymph node (LN) involvement were independent factors for pulmonary malignancy development, and they led to the hypothesis that the lower cervical LN near the thoracic space would be at significant risk for lung metastases based on the “cascade theory”, which infers that some adjacent sites are seeded first and that further metastases proceed in sites other than the primary site. 17 Additionally, primary cervical LN involvement was demonstrated to be a poor prognostic factor after PM for HNSCC.…”
Section: Discussionmentioning
confidence: 99%
“… 17 Advanced primary stage and primary cervical lymph node (LN) involvement were independent factors for pulmonary malignancy development, and they led to the hypothesis that the lower cervical LN near the thoracic space would be at significant risk for lung metastases based on the “cascade theory”, which infers that some adjacent sites are seeded first and that further metastases proceed in sites other than the primary site. 17 Additionally, primary cervical LN involvement was demonstrated to be a poor prognostic factor after PM for HNSCC. 5 , 6 , 18 These data suggest that primary site cervical LN involvement might have a significant effect on pulmonary metastases and might be associated with a poor prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…After a mean time of 18 months, another 14% of our patients developed metachronous distant metastatic outgrowth, in particular pulmonary metastases. The diagnostic gap in the pre-therapeutic identification of pulmonary metastases was recently demonstrated [ 17 ] and highlights the necessity to identify molecular markers that predict both, local and systemic tumor recurrency at the time of initial diagnosis. Recently, CXCR4 came into focus in different tumor entities and CXCR4-positivity was usually associated with local tumor growth, the occurrence of local and systemic metastases and, therefore, reduced survival parameters [ 14 ].…”
Section: Discussionmentioning
confidence: 99%